Beta adrenergic receptors in pigmented ciliary processes. Issue 12 (December 1982) - Trope, G E; Clark, B
Abstract : Beta adrenergic receptors from membrane fragments of pigmented sheep eyes were studied and characterised by ligand binding techniques after the removal of melanin. In a representative experiment the beta max (total number of beta receptors) was 394.9 fmol/mg protein. The receptor affinity (Ka) was 440 pM. The potency series of drugs to displace 125I-HYP from the receptors was timolol = (-) propranolol greater than (+) propranolol greater than salbutamol greater than practolol. beta 1 Receptors were not detected in the ciliary processes. beta 2 Receptors were the prominent adrenergic receptors present. The theory as to how beta blockers work in glaucoma, their site of action, and the potential role of beta 2 blockers for use in intraocular pressure control is discussed.